International environmental law reports (Cambridge University Press, 2001)
Trade and Environment provides a complete set of the major dispute settlement or judicial decisions on environment-related issues under three international trade regimes: the General Agreement on Tariffs and Trade (GATT) and its successor the World Trade Organization (WTO); the Canada-USA Free Trade Agreement (precursor to the North America Free Trade Agreement); and the European Community. It also provides extracts from other cases dealing with issues relevant to future trade and environment controversies. A convenient compendium for policy makers in government and NGOs, academic researchers, students, and business advisors.